ANALYSIS OF THE EFFECT OF SUKUK IJARAH ISSUANCE ON THE PROFITABILITY OF COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2018-2021 PERIOD - Fathia Hidayat; Zuwardi Zuwardi (CV. Adiba Aisha Amira, 2023)
This thesis is entitled